Dying in the Intensive Care Unit (ICU): A Retrospective Descriptive Analysis of Deaths in the ICU in a Communal Tertiary Hospital in Germany - Esma Ay; Markus. A. Weigand; Rainer Röhrig; Marco Gruss (Anesthesiology Research and Practice)
Background. Modern intensive care methods led to an increased survival of critically ill patients over the last decades. But an unreflected application of modern intensive care measures might lead to prolonged treatment for incurable diseases, and an inadaequate or too aggressive therapy can prolong the dying process of patients. In this study, we analysed end-of-life decisions regarding withholding and withdrawal of intensive care measures in a German intensive care unit (ICU) of a communal tertiary hospital. Methods. Patient datasets of all adult patients dying in an ICU or an intermediate care unit (IMC) in a tertiary communal hospital (Klinikum Hanau, Germany) between 01.01.2011 and 31.12.2012 were analysed for withholding and withdrawal of intensive care measures. Results. During the two-year period, 1317 adult patients died in Klinikum Hanau. Of these, 489 (37%) died either in an ICU/IMC unit. The majority of those deceased patients (n = 427, 87%) was 60 years or older. In 306 (62%) of 489 patients, at least one life-sustaining measure was withheld or withdrawn. In 297 (61%) of 489 patients dying in ICU/IMC, any type of therapy was withheld, and in 139 patients (28%), any type of therapy was withdrawn. Mostly, cardiopulmonary resuscitation (n = 222), invasive (n = 121) and noninvasive (n = 40) ventilation followed by renal replacement therapy (n = 71) and catecholamine therapy (n = 66) were withheld. More invasive measures as ventilation or renal replacement therapy were withdrawn in 18 and 22 patients only. After withholding/withdrawal of therapy, most patients died within two days. More than 20% of patients dying in ICU/IMC did not have an analgesic medication. Conclusions. About one-third of patients dying in the hospital died in ICU/IMC. At least one life-sustaining therapy was limited/withdrawn in more than 60% of those patients. Withholding of a therapy was more common than active therapy withdrawal. Ventilation and renal replacement therapy were withdrawn in less than 5% of patients, respectively.